Weak correlation of bleeding scores to platelet electron microscopy: A retrospective chart review of pediatric patients with delta‐storage pool disorder. Issue 3 (21st October 2018) - Nessle, C. N.; Ghosal, S.; Mathews, C.; Taylor, D.; Myers, J.; Raj, A.; Panigrahi, A.
Abstract: Background: Delta granule storage pool deficiency (δ‐SPD) is a rare platelet disorder in which a deficiency of platelet granules leads to poor aggregation, resulting in varying clinical bleeding phenotypes. Children with δ‐SPD have variable laboratory results, making the proper diagnosis and evaluation controversial. Objectives: To describe the demographic and laboratory trends of this population and to assess the value of electron microscopy in diagnostic evaluation and its correlation to bleeding symptoms. Methods: We performed a retrospective review of 109 pediatric patients diagnosed with δ‐SPD. We collected demographic information and bleeding scores using a validated bleeding assessment tool. A descriptive and exploratory analysis was performed. Results: The majority of patients were female, with an average age at diagnosis of 11.61 years. Females were diagnosed at a significantly older age presenting most often with menorrhagia, while males presented most commonly with epistaxis. The majority showed normal lumiaggregometry, the mean platelet electron microscopy (PEM) value was 2.37, and the mean bleeding score was 6. Bleeding assessment tool and PEM had a significantly weak correlation. Conclusions: Patients with more dense granules per platelet had higher bleeding scores than those with fewer dense granules per platelet. The current body of evidence does not favor the use of PEM in routine clinical practice, and results are difficult to interpret. In patients with severe mucocutaneous bleeding symptoms and normal platelet aggregation studies, consideration should be given to an alternative diagnosis and further evaluation is warranted.